Development of a Cryptography Secured E-Administration System - Ohwobeno, Omohwo; Iwasokun, Gabriel Babatunde; Adegoke, Michael Abejide; Agbelusi, Olutola; David, Bamidele; Ibraheem, Temitope (European Journal of Applied Sciences, 2024)
This paper presents the design of the e-administration platform that adopts the concept of cryptography for identity management. The architectural framework of the platform comprises subcomponents for service and forms identification, business process redesign, service architecture, amalgamation, and deployment. The cryptography model for securing the platform was designed based on the combination of authentication criteria presented in the Rijndael-Advanced Encryption Standard (AES), Lattice-based cryptography (LBC), and Secure Hash Algorithm (SHA512). It is required that a record be encrypted prior to its commitment to the database via a double encryption method. The AES algorithm-based encryption’s output formed the input to the LBC algorithm to obtain the final output. Five text files of varying sizes were used to evaluate the performance of the AES, GGH, and the Hybrid Encryption Algorithm (HEA). The evaluation of the algorithms focused on three key parameters; namely encryption time, decryption time, and the size of the encrypted file. Results showed that the time taken by the HEA encryption algorithm encryption and decryption processes is significantly higher compared to the time taken by the AES and GGH algorithms. This suggests that the HEA takes longer times and hence will be more difficult for intruders to manipulate or read.